Pemberdayaan Masyarakat Perkotaan Melalui Pemanfataan Lahan Perkarangan Untuk Meningkatkan Ketahanan Pangan dan Kesejahteraan Masyarakat di Kabupaten Aceh Besar - Mujiburrahmad; Ira Manyamsari; Romano; Noratun Juliaviani; Edy Marsudi (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this community service is to increase the knowledge, attitudes and skills of PKK mothers in Gue Gajah Village regarding verticulture shelf assembly techniques, proper business management, diversification of verticultural processed food and professional marketing using a mobile application. Implementation activities will begin with the coordination and socialization stage with partners for the implementation of activities, then proceed with training on diversification of processed food products. The next activity is to provide counseling on business management, and ways to develop it. Providing counseling on business management, and ways to develop it. Furthermore, partners will be facilitated in making mobile application digital marketing applications so as to facilitate the marketing process. Based on the results of the activity, it can be concluded that partners have increased their knowledge and skills in improving horticultural cultivation vertically. Long-term planning on the use of a marketing android application to increase sales of vegetables. This application is expected to be one of the models in tools for marketing vegetable products in Banda Aceh and Aceh Besar. The continuation of this program can also be carried out by forming partners or partners for Study Programs within the University of Syiah Kuala to support the Independent Learning Campus Merdeka (MBKM) program. Students will later do an internship at Dudi Partners with conditions that have been agreed upon by both parties.